Responsibility and Intervening Acts: What “Maybin” an Overbroad Approach to Causation - Skolnik, Terry (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2014)
Oftentimes, a criminal action resulting in the victim’s death is clearly attributable to the accused. In many cases, we can easily say that the accused “caused” the victim’s death. Causation, however, becomes particularly complicated when some type of intervening act occurs between the accused’s initial conduct and the victim’s death, creating speculation about whether it is fair to morally blame the accused for the ensuing result. The Supreme Court of Canada’s relatively recent decision R v Maybin marks a significant attempt to clarify notions related to causation in the criminal law. Although the Court refused to alter conventional principles related to the law of causation, or create a new test to verify when it has been established, it provided two analytical tools which can be used in order to see when it is fair to morally blame the accused for the victim’s death despite an intervening act’s occurrence. As will be seen, although these analytical tools of “reasonable foreseeability” and “independent acts” serve to simplify the law of causation, there are important problems with how each tool has been conceptualized. This article highlights these important shortfalls, and ultimately, questions to what extent these developments in the law of causation affect current conceptions of mens rea.